Novel Anticancer Fused Pyrazole Derivatives as EGFR and VEGFR-2 Dual TK Inhibitors - Saleh, Nashwa M.; El-Gazzar, Marwa G.; Aly, Hala M.; Othman, Rana A. (Frontiers in Chemistry, 2020)
EGFR and VEGFR-2 represent promising targets for cancer treatment as they play a crucial role in tumor growth, angiogenesis and metastasis. In this work, 6-amino-4-(2-bromophenyl)-3-methyl-1,4-dihydropyrano[2,3-c]pyrazole-5-carbonitrile 1 and (E)-4-(2-Bromobenzylidene)-5-methyl-2,4-dihydro-3H-pyrazol-3-one 11 were selected as starting materials to synthesize different fused pyrazole derivatives; dihydropyrano[2,3-c]pyrazole 1, 2, 7-9 and 15, pyrazolo[4',3':5,6]pyrano[2,3-d]pyrimidine 3-6, pyrazolo[3,4-d]pyrimidine 12 and 13 and pyrazolo[3,4-c]pyrazole 14 derivatives were synthesized to evaluate their anticancer activity against HEPG2 human cancer cell line compared to erlotinib as reference drug. Seven compounds 1, 2, 4, 8, 11, 13 and 15 showed nearly 10-folds higher activity than erlotinib (10.6 µM) with IC50 ranging from 0.31 to 0.71 µM. In vitro EGFR and VEGFR-2 inhibitory activity was performed for the synthesized compounds, the results identified compound 3 as the most potent EGFR inhibitor (IC50= 0.06 µM) and compound 9 as the most potent VEGFR-2 inhibitor (IC50= 0.22 µM). Moreover, compounds 9 and 13 revealed potent dual EGFR and VEGFR-2 inhibition these results were supported by docking studies of these two compounds within the active sites of both enzymes.